World State versus Federation of States. Did Kant intentionally offer a free choice to future scholars? - Blomme, Henny (Studia Kantiana, 2023)
It is well-known that Kant's short treatise Zum ewigen Frieden contains some ambiguities concerning the kind of political constellation we should strive for in order to establish perpetual peace. A first option would be to strive for an all-encompassing republican world-state. Once such a world-state has been established, the former individual states lose not only their sovereignty, but also their right of sovereignty. A second option would be to strive for a free confederation of sovereign states. In this case, the states do not abolish their sovereignty, and the confederation is the result of a contract between the states that is upheld as long as the representative power of those states decides not to withdraw from it. In this contribution, I ask whether Kant's notorious ambiguity on the question "world republic or federation of states?" can be said to be strategic.